Pengaruh Rasio Liquiditas terhadap Rasio Profitabilitas pada PT. Adira Dinamika Multifinance, Tbk di Jakarta Periode 2011-2020 - Siti Nurcahayati (Jurnal Tadbir Peradaban, 2021)
This study aims to determine the effect of the Current Ratio on Return On Assets at PT. Adira Dinamika Multifinance, Tbk in Jakarta. The method used is explanatory research. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this research variable Current Ratio obtained an average value of 127.57%. The Return On Assets variable obtained an average value of 72.36%. Current Ratio has a positive and significant effect on Return On Assets with a regression equation value of Y = 24,643 + 0.374X, and a correlation coefficient value of 0.878 or has a strong relationship with a determination value of 77.1%. Hypothesis testing obtained a significance of 0.001 <0.05.